2020
DOI: 10.1093/sleep/zsaa024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of REM sleep behavior disorder in Japanese elderly people

Abstract: Study Objectives To evaluate the prevalence and clinical characteristics of isolated REM sleep behavior disorder (iRBD) among a general population of elderly Japanese people. Methods This epidemiological study targeted 2714 elderly residents (76.0 ± 8.0 years, 52.9% female) of a rural community. Questionnaires including the REM sleep behavior disorder single question and demographic information were distributed. All responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Nutritional status and sleep quality are the two cornerstone factors that comprehensively affect the physical and mental health of the elderly. Their poor condition can lead to comprehensive health consequences such as depression, anger, muscle tension, sympathetic excitement, cognitive disorders, neurological disorders, gastrointestinal, and upper respiratory tract diseases, and even cardiovascular and cerebrovascular injury (4)(5)(6). However, there are only a limited number of studies focused on nutrition and sleep status in the healthy elderly, especially centenarians.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status and sleep quality are the two cornerstone factors that comprehensively affect the physical and mental health of the elderly. Their poor condition can lead to comprehensive health consequences such as depression, anger, muscle tension, sympathetic excitement, cognitive disorders, neurological disorders, gastrointestinal, and upper respiratory tract diseases, and even cardiovascular and cerebrovascular injury (4)(5)(6). However, there are only a limited number of studies focused on nutrition and sleep status in the healthy elderly, especially centenarians.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many recent studies have used a multistep approach including questionnaires and polysomnography to detect RBD. 13,[21][22][23] Although multistep screening for RBD could lead to false negatives if participants are not aware of their RBD symptoms, 1 this approach reduces the number of required polysomnographies and increases the validity of the diagnosis. Studies using a stepwise approach have shown highly similar RBD prevalences to polysomnography studies in a random sample, supporting the accuracy of this approach.…”
Section: Rbd Screening In Population-based Studiesmentioning
confidence: 99%
“…Little is known about how previous polysomnography studies handled disclosure of RBD diagnosis or the concurrent risk of α-synucleinopathies to participants. [11][12][13][21][22][23] One study in which participants responded to a newspaper advertisement including an RBD screening question described that a study neurologist discussed the RBD diagnosis and associated risk of α-synucleinopathies in a face-to-face consultation. 22 The risk information was communicated after extensive history taking and neurological examination, and the participants were offered annual follow-up by the study neurologist.…”
Section: Risk Disclosurementioning
confidence: 99%
See 2 more Smart Citations